Virtual study abroad: A case study - Lipinski, John; Fojtik, János (Marketing & Menedzsment, 2019)
Over 90 percent of US universities sponsor study abroad programs. Students are encouraged to engage in such programs to enhance their educational experience and increase their global awareness in our interconnected world. However, despite these efforts, students who engage in such programs are a rarity. Only 1% of US students pursue a study abroad experience each academic year. In order to address this and make key aspects of the study abroad experience available to a wider range of students, two professors decided to link their classrooms, separated by 5,102 miles, via teleconference and create a virtual study abroad class.